Development and validation of liquid chromatography tandem mass spectrometry method for determination of rivaroxaban in plasma samples - Crevar, Milkica; Miličević, Maja; Ivković, Branka; Džudović, Jelena (Archives of Pharmacy, 2022)
Rivaroxaban belongs to the group of direct oral anticoagulants (DOAC), drugs used to prevent and treat venous thrombosis and venous thromboembolism. Drugs from this group are considered safer than vitamin K antagonists. In case of overdose, their most significant side effect is bleeding. Given the great toxicological significance, it is very important to develop an analytical method for quantification of this drug in biological samples. The liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for the determination of rivaroxaban content in plasma samples was optimized and validated. Plasma samples were prepared by protein precipitation with cold acetonitrile. Carbamazepine was used as an internal standard. The analysis was performed on an Infinity Lab Poroshell 120 EC-C18, 4.6 ×100 mm, 2.7 μm chromatographic column. The mobile phase consisted of acetonitrile and 0.1% formic acid (50:50, v/v), at a flow rate of 400 μL/min and a column temperature set at 30°C. The autosampler temperature was 4°C. The injection volume was 10 μL. Detection of analytes and internal standard was performed in multireaction monitoring mode (MRM), at the following ion transitions: 437>145 (m/z) for rivaroxaban, and 237>194 (m/z) for the internal standard. The optimized method was validated and the obtained parameters indicate that the method is sensitive, specific, selective, precise and accurate. The samples were stable under the tested conditions. A validated method has been used to determine the concentration of rivaroxaban in plasma samples of patients with atrial fibrillation who were hospitalized under strict medical supervision. Obtained concentrations were in the expected range.